2006
DOI: 10.1530/rep.1.00941
|View full text |Cite
|
Sign up to set email alerts
|

Role of the N, N′-dimethylbiguanide metformin in the treatment of female prepuberal BALB/c mice hyperandrogenized with dehydroepiandrosterone

Abstract: The present study investigated the role of the N, N{ 0 }-dimethylbiguanide metformin (50 mg/100 g body weight in 0.05 ml water, given orally with a canulla) in the prevention of endocrine and immune disorders provoked by the hyperandrogenization with dehydroepiandrosterone (DHEA) in prepuberal BALB/c mice. The treatment with DHEA (6 mg/100 g body weight in 0.1 ml oil) for 20 consecutive days, recreates a mouse model that resembles some aspects of the human polycystic ovary syndrome (PCOS). The treatment with D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
76
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 74 publications
13
76
1
Order By: Relevance
“…DHEA restores the cell-mediated immune response of pro-inflammatory cytokines (IL-1, IL-6, TNF-α, and IL-18). Mice treated with DHEA exhibited increased production of cytokines such as serum TNF-α, IL-6, IL12p70, and IFN-γ (82,83). DHEA supplementation also increases vascular cell adhesion molecule 1 (VCAM-1) and intercellular cell adhesion molecule 1 (ICAM-1) in the granulosa cell layer of cysts and the theca cell layer of all follicles and cysts when DHEA androgenization induces the formation of cysts (83).…”
Section: Balance Of the Th1 And Th2 Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…DHEA restores the cell-mediated immune response of pro-inflammatory cytokines (IL-1, IL-6, TNF-α, and IL-18). Mice treated with DHEA exhibited increased production of cytokines such as serum TNF-α, IL-6, IL12p70, and IFN-γ (82,83). DHEA supplementation also increases vascular cell adhesion molecule 1 (VCAM-1) and intercellular cell adhesion molecule 1 (ICAM-1) in the granulosa cell layer of cysts and the theca cell layer of all follicles and cysts when DHEA androgenization induces the formation of cysts (83).…”
Section: Balance Of the Th1 And Th2 Immune Responsementioning
confidence: 99%
“…Extrathymic (DP) CD4+/ CD8+ T cells positively correlated with circulating levels of TNF-α and with the cortisol/DHEAs ratio (87). Flow cytometry showed that DHEA treatment in mice significantly increased the CD4+ lymphocyte population and decreased the CD8+ lymphocyte population, thus modulating the CD4+/CD8+ lymphocyte balance in both ovarian tissue and retroperitoneal lymph nodes (82). This may be due to the selective T lymphocyte infiltration of ovarian tissue (88).…”
Section: Balance Between Cd4+/cd8+ T Cellsmentioning
confidence: 99%
“…The dose of DHEA injected was that previously used by Lee et al (1991Lee et al ( , 1998, Henmi et al (2001), Luchetti et al (2004), Sander et al (2005Sander et al ( , 2006, Elia et al (2006) and Solano et al (2006) and ensure a hyperandrogenized status. The dose of metformin administered was ensured to that used in the treatment of women with PCOS.…”
Section: Experimental Designmentioning
confidence: 99%
“…Postnatal treatment of mice [47,48] and rats [44][45][46] with DHEA for 20 consecutive days resulted in all or most females exhibiting follicular cysts with a thin granulosa cell layer and anovulation. Ovaries exhibited an increase in fat and stroma tissues and increased numbers of atretic follicles [48,49], hyperandrogenism, and altered ovarian steroidogenesis with elevated serum levels of androgens [44,48,50], estrogens, P, and prostaglandin [44,47,49,50].…”
Section: Rodent Models Of Pcosmentioning
confidence: 99%
“…Ovaries exhibited an increase in fat and stroma tissues and increased numbers of atretic follicles [48,49], hyperandrogenism, and altered ovarian steroidogenesis with elevated serum levels of androgens [44,48,50], estrogens, P, and prostaglandin [44,47,49,50]. In one study, LH levels were elevated while follicle-stimulating hormone (FSH) levels did not change [44], but in other studies, LH and FSH levels were both decreased [46] or unchanged [50].…”
Section: Rodent Models Of Pcosmentioning
confidence: 99%